1981
DOI: 10.1128/iai.33.2.583-590.1981
|View full text |Cite|
|
Sign up to set email alerts
|

Detection of extracellular toxin(s) produced by Vibrio vulnificus

Abstract: Conditions are described for the production, in high titers, of heat-labile, antigenic, extracellular toxin(s) by Vibrio vulnificus, a recently recognized human pathogen. Bacteriologically sterile culture filtrate preparations obtained from mid-logarithmic-phase cultures of the bacterium possessed cytolytic activity against mammalian erythrocytes, cytotoxic activity for Chinese hamster ovary cells, vascular permeability factor activity in guinea pig skin, and lethal activity for mice. The specific activity of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
89
0

Year Published

1983
1983
2002
2002

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 197 publications
(92 citation statements)
references
References 23 publications
3
89
0
Order By: Relevance
“…The importance of exotoxin in the pathogenicity of vibriosis in man has been demonstrated in V. cholerae (5) and V. mimicus (1). Production of exotoxin by halophilic vibrios has been reported in V. anguillarum (6,13,19), V. parahaemolytic u s (17), V. vulnificus (9), and V. fluvialis (10). In the previous study, we found that the culture filtrate of V. anguillarum contains a substance lethal to mice and rainbow trout (8,12).…”
Section: Discussionmentioning
confidence: 99%
“…The importance of exotoxin in the pathogenicity of vibriosis in man has been demonstrated in V. cholerae (5) and V. mimicus (1). Production of exotoxin by halophilic vibrios has been reported in V. anguillarum (6,13,19), V. parahaemolytic u s (17), V. vulnificus (9), and V. fluvialis (10). In the previous study, we found that the culture filtrate of V. anguillarum contains a substance lethal to mice and rainbow trout (8,12).…”
Section: Discussionmentioning
confidence: 99%
“…A number of factors have been implicated as contributing to disease caused by V. vulnificus, such as iron availability in human serum for their survival (Wright et al 1981) ; the presence of a cytolysin that lyses red blood cells and is cytotoxic for Chinese hamster ovary (CHO) cells, enhances vascular permeability in guinea pig skin and is lethal for mice (Kreger and Lockwood 1981) ; proteases like collagenase (Smith and Merkel 1982) and elastase (Kothary and Kreger 1985) ; phospholipases and chondroitin-sulphatase (Oliver et Correspondence to: M. Landgraf, Faculdade de Ci锚ncias Farmac锚uticas, USP, Av. Prof. Lineu Prestes 580, Bloco 14, S茫o Paulo, Brazil, CEP 05508-900.…”
Section: Introductionmentioning
confidence: 99%
“…V. vulnificus, a pathogenic bacterium found in estuarine and coastal regions, produces a heat-labile hemolysin [1][2][3][4]. Gray and Kreger [3] and Shinoda et al [4] reported that VVH was inactivated by addition of cholesterol.…”
Section: Introductionmentioning
confidence: 99%